Impact of kurera/ukondla youth fund on youth empowerment in Warren Park, Harare - Mhasvi, Joseph (Midlands State University, 2017)
This research sought to investigate the impact of Kurera/Ukondla youth fund on youth empowerment in Warren Park. The researcher further explored how the government and other youth based institutions can assist youths to reach their full potentialities. The researcher has deliberated on the role of the government in meeting the needs of the youths in Warren Park and in Zimbabwe at large. Youths face different problems in Zimbabwe such as unemployment, underemployment, lack of access to credits amongst others and the researcher has offered possible solutions that can be employed if meaningful youth empowerment in Zimbabwe is to be achieved. The study used cases of youth projects funded under the Kurera/Ukondla youth fund in Warren park. It made use of the qualitative research method to understand the lives of the youths before and after the youth fund and also to understand the effectiveness of the Kurera/Ukondla youth fund as far as youth empowerment in Warren Park is concerned. Data has been collected from the beneficiaries and applicants of the fund in Warren Park. The researcher in this research has also deliberated on the challenges that youths in Warren Park faced in accessing and utilising the Kurera/Ukondla youths fund as these hampered the success of the fund. After the realisation of multiple challenges, this research therefore offered solutions that can be employed in order to make other youth funding projects a success.